2021
DOI: 10.3390/polym13101619
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Morphological Composition of Norway Spruce Wood (Picea abies, L.) in the Dependence of Its Storage

Abstract: Chemical composition and morphological properties of Norway spruce wood and bark were evaluated. The extractives, cellulose, hemicelluloses, and lignin contents were determined by wet chemistry methods. The dimensional characteristics of the fibers (length and width) were measured by Fiber Tester. The results of the chemical analysis of wood and bark show the differences between the trunk and top part, as well as in the different heights of the trunk and in the cross section of the trunk. The biggest changes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 21 publications
3
13
0
Order By: Relevance
“…This sample also has the lowest proportion of saccharides, mainly due to the degradation of hemicelluloses (C/H ratio = 1.09). Several authors describe the decrease of polysaccharides during natural aging of wood [ 45 , 57 ]. Therefore, older wood poses a greater risk of ignition compared to the younger oak wood.…”
Section: Resultsmentioning
confidence: 99%
“…This sample also has the lowest proportion of saccharides, mainly due to the degradation of hemicelluloses (C/H ratio = 1.09). Several authors describe the decrease of polysaccharides during natural aging of wood [ 45 , 57 ]. Therefore, older wood poses a greater risk of ignition compared to the younger oak wood.…”
Section: Resultsmentioning
confidence: 99%
“…In the cases of lignin content of 2-year-old and extractive content of 3-year-old, our findings are not in agreement because they tended to decrease from the bottom towards the top. According to Cabalová et al (2021), the extractive content of both wood and bark increases vertically from the base toward to top part of the tree. On the other hand, Roitto et al (2016) found that the extractive content in birch stem wood rises from the bottom toward the top.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Routa et al studied Pinus sylvestris and Picea abies bark in pile storage and found that only 56% and 66% of the acetone-soluble extractives remained after eight weeks of storage, respectively [23,24]. Čabalova et al also reported a significant decrease in Picea abies bark extractives extracted by ethanol-toluene mixture (2:1) and a relative increase in lignin and cellulose during 8 months of storage [25]. Compared to our previous study regarding Picea abies sawlog bark storage in winter and summer, the difference was noticeable.…”
Section: Change In Total Dissolved Solids the Effect Of Storage Timementioning
confidence: 95%